PENGGUNAAN TYPE JIGSAW DALAM ILMU PENGETAHUAN ALAM UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Agustinus, Agustinus; Kresnadi, Hery; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
The purpose of this research is to know how the use of cooperative learning jigsaw type in science learning to increase students? learning outcomes. The method of this research is action classroom research. The subject of this research is fourth grade students of SD Negeri 03 Bengkayang. This research is done in three cycle where in each has one phase: preparation, implementation, observation, and reflection. Technique of data collecting in this research is IPKG I, IPKG II, and evaluation. Technique of analysis data used is qualitative and quantitative. Based on the data analysis, teacher ability on planning and implementing of science learning is improved. In the first cycle, the score of teacher ability on planning is 2.16 point, 2.82 point, and the third cycle is 3.72 point. Meanwhile, on the teacher implementation, the score in the first cycle is 1.76 point, the second cycle is 2.92 point, and the third cycle is 3.93 point. The result of students? evaluation is 42.42% students get 62.42 in the first cycle, 66.67% students get 68.78, and 100% students get 75.75. In conclusion, jigsaw type can improve students? learning outcomes in science learning. Keywords : Improving, Jigsaw Type, Learning Outcomes